Using Expert Opinion to Quantify Uncertainty in and Cost of Using Nondestructive Evaluation on Bridges - Alex A. Hesse; Rebecca A. Atadero; Mehmet E. Ozbek (Advances in Civil Engineering)
A previous literature review indicated that there is little published experimental data that can be used to determine quantities such as bias, accuracy, reliability, and cost of common Nondestructive Evaluation (NDE) methods as far as their use on bridges is concerned. This study attempts to quantify these parameters for common bridge NDE methods through a four-round Delphi method survey with experts in the NDE bridge field. The survey results indicate that most commonly used bridge NDE methods tend to be underbiased and relatively reliable. Furthermore, the accuracy of commonly used bridge NDE methods tends to be relatively variable with the average test measuring a true response between 80% and 85% of the time. In general, it was shown by the participant responses that the more expensive the method was, the better the bias, accuracy, and reliability the method had, and vice versa. The information presented in this paper can serve as a starting point for characterizing different NDE methods for use in bridge management and inspection planning and identifies the type of information that is still needed. As such, this research has the potential to promote further research on this subject.